The effects of gender discrimination on medical students‘ choice of specialty for their (junior) residency – a survey among medical students in Germany - Stock, Jule; Kaifie, Andrea (BMC Medical Education, 2024)
Background: Gender discrimination is known to affect societies in many different settings. Medical education is no exception. This study focusses on the consequences, gender discrimination can have on medical students and their choice of (junior) residency specialty. Methods: An online questionnaire was developed and distributed among the 40 medical faculties in Germany. The study population contained medical students in their fifth and sixth academic year. Results: The survey’s participants consisted of 759 students from 31 universities. Female medical students experienced significantly more gender discrimination compared to their male colleagues (f = 487, 87.9% vs. m = 76, 45.8%, p < 0.0001). The specialties with the most reported gender discrimination were family medicine (f = 180, 42.9% vs. m = 15, 23.8%, p < 0.05), followed by surgery (f = 369, 87.4% vs. m = 44, 69.8%, p < 0.05), internal medicine (f = 282, 67.3% vs. m = 37, 58.7%, ns), orthopaedics/casualty surgery (f = 270, 65.1% vs. m = 32, 50.8%, p < 0.05), and gynaecology (women (f = 142, 34.1% vs. m = 34, 54.0%, p < 0.05). Gynaecology was the only specialty, men experienced more discrimination compared to women. Among the students that ever changed their specialty of choice (f = 346 (73.3%) m = 95 (72%)), significantly more women than men claimed gender discrimination to be one of the main three reasons for their specialty choice (f = 42, 12.1% vs. m = 1, 1.1%, p < 0.05). In addition, 53 students (f = 50 (10.6%) m = 3 (2.3%)) stated to rule out a specialty from the beginning due to gender discrimination. Conclusion: Gender discrimination is frequently experienced by medical students in Germany. It influences their choice of medical specialty directly. Our data suggest a fundamental problem that proposes and implicates certain specialties to be attractive for only one gender.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Degradation; Harassment; Medical education; Sexism